2022
DOI: 10.3390/polym14040801
|View full text |Cite
|
Sign up to set email alerts
|

Study of Protective Layers Based on Crosslinked Glutaraldehyde/3-aminopropyltriethoxysilane

Abstract: In this paper, we report the synthesis and characterization of novel coatings based on (3-Aminopropyl)-triethoxysilane (AP) mixed with different amounts of glutaraldehyde (GA). The synthesized coatings have been layered on a glass substrate and characterized by optical microscopy and roughness measurements, thermogravimetric analyses and differential scanning calorimetry, contact angle analysis, rheological measurement, and an adhesion test. It was observed that the higher the GA content (up to AP:GA ratio of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
(33 reference statements)
0
8
0
Order By: Relevance
“…Several studies have been published in literature with the aim to produce new ecofriendly coatings with chemical green features and appreciable physic-mechanical performances [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been published in literature with the aim to produce new ecofriendly coatings with chemical green features and appreciable physic-mechanical performances [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been published in the literature with the aim of producing ecofriendly coatings with chemical green features and excellent physical-mechanical performance [16][17][18][19][20][21][22]. Among the permissible materials, nanocomposites based on Cu/TiO 2 and Ag/TiO 2 oxides with a low metal content (≤5 wt%) have been studied for their antifouling properties.…”
Section: Introductionmentioning
confidence: 99%
“…It can construct rough structures on the substrate's surface, achieving excellent hydrophobic effects. In reports, it is generally functionalized by hydrophobic modifiers with low surface energy, for instance, fluorinated alkylsilanes (FAS) [20], hexadecyltrimethoxysilane (HDTMS) [21], and aminopropyltriethoxysilane (AP) [22] et al Of these, fluorinated alkylsilanes are interesting in decreasing surface energy because of the specific characteristics of their fluorine atoms. It has also been reported that when surfaces are abundant in CF 3 groups, fluorinated compounds can decrease the surface tension to ~6.7 mN/m, which is significantly lower than the surface tension of water (~72.8 mN/m at room temperature) [23].…”
Section: Introductionmentioning
confidence: 99%